Tahlîl Al-Asâlîb Al-Insyâiyyah Al-Talâbiyah Fî Sûrah Ibrâhîm wa Al-Istifâdah minhâ Li-Ta‘lîm Al-Lughah Al-‘Arabiyyah li-Ghayr Al-Nâṭiqīn bihâ - Masri, Muh. Miswal; Moh. Abdul Kholiq Hasan (Institut Muslim Cendekia, 2025)
An important aspect to consider in teaching and learning Arabic for non-native speakers is al-asalib al-insha’iyyah al-talabiyyah, as this method helps both teachers and learners facilitate Arabic language acquisition and understanding of the Qur’an. This study aims to identify the Qur’anic verses that contain al-asalib al-insha’iyyah al-talabiyyah in Surat Ibrahim. The researcher used a qualitative descriptive-analytical method by studying and collecting data from available library resources such as tafsir books and rhetoric (balaghah) literature, then gathering the relevant data. The study found the following results: al-asalib al-insha’iyyah al-talabiyyah appeared in 37 instances in Surat Ibrahim. The uslub al-amr appeared in verses 5, 6, 10, 22, 30, 31, 35, 37, 40, and 44. The uslub al-istifham appeared in verses 9, 10, 12, 19, 21, 24, 28, and 44. The uslub al-nahy appeared in verses 22 and 42. The uslub al- appeared in verses 35, 36, 37, 38, 40, 41, and 44. Meanwhile, the uslub al-tamanni was not found in Surat Ibrahim. The utilization of al-asalib al-insha’iyyah al-talabiyyah in Surat Ibrahim for teaching Arabic to non-native speakers can be applied by incorporating them into exercises such as questions, dialogues, texts, sentence formation using the targeted styles, and other training activities.